Role of Lysozyme Inhibitors in the Virulence of Avian Pathogenic Escherichia coli - Vanderkelen, Lise (Public Library of Science, 2012)

(untitled)
Lysozymes are key effectors of the animal innate immunity system that kill bacteria by hydrolyzing peptidoglycan, their major cell wall constituent. Recently, specific inhibitors of the three major lysozyme families occuring in the animal kingdom (c-, g- and i-type) have been discovered in Gram-negative bacteria, and it has been proposed that these may help bacteria to evade lysozyme mediated lysis during interaction with an animal host. Escherichia coli produces two inhibitors that are specific for c-type lysozyme (Ivy, Inhibitor of vertebrate lysozyme; MliC, membrane bound lysozyme inhibitor of c-type lysozyme), and one specific for g-type lysozyme (PliG, periplasmic lysozyme inhibitor of g-type lysozyme). Here, we investigated the role of these lysozyme inhibitors in virulence of Avian Pathogenic E. coli (APEC) using a serum resistance test and a subcutaneous chicken infection model. Knock-out of mliC caused a strong reduction in serum resistance and in in vivo virulence that could be fully restored by genetic complementation, whereas ivy and pliG could be knocked out without effect on serum resistance and virulence. This is the first in vivo evidence for the involvement of lysozyme inhibitors in bacterial virulence. Remarkably, the virulence of a ivy mliC double knock-out strain was restored to almost wild-type level, and this strain also had a substantial residual periplasmic lysozyme inhibitory activity that was higher than that of the single knock-out strains. This suggests the existence of an additional periplasmic lysozyme inhibitor in this strain, and indicates a regulatory interaction in the expression of the different inhibitors.